NONLEPTONIC ANNIHILATION DECAYS of B MESON WITH A NATURAL INFRARED CUTOFF - Natale, Adriano Antonio [UNESP]; Zanetti, C. M. [UNESP] (World Scientific Publ Co Pte Ltd, 2009)
Within the QCD factorization approach we compute the amplitudes for pure annihilation channels of B mesons decays into final states containing two pseudoscalar particles. These decays may be plagued by effects like nonperturbative physics and breaking of the factorization hypothesis and imply, at some extent, the introduction of an infrared cutoff in the calculation of amplitudes. We compute the decays with the help of infrared finite gluon propagators and coupling constants that were obtained in different solutions of the QCD Schwinger-Dyson equations. These solutions yield a natural cutoff for the amplitudes, and we argue that a systematic study of these B decays may provide a test for the QCD infrared behavior.
Keywords: B meson; hadronic decays; infrared cutoff